2008
DOI: 10.1093/ije/dyn079
|View full text |Cite
|
Sign up to set email alerts
|

Systematic differences in treatment effect estimates between propensity score methods and logistic regression

Abstract: Propensity score methods give in general treatment effect estimates that are closer to the true marginal treatment effect than a logistic regression model in which all confounders are modelled.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
107
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(110 citation statements)
references
References 28 publications
3
107
0
Order By: Relevance
“…These methods produced similar results and were also approximately equally precise. These findings correspond to previous studies indicating that these methods give approximately the same results [10,[27][28][29]. Propensity score methods can be useful to reduce the number of covariates to be included in a multivariable model in case of limited sample size.…”
Section: Discussionsupporting
confidence: 90%
“…These methods produced similar results and were also approximately equally precise. These findings correspond to previous studies indicating that these methods give approximately the same results [10,[27][28][29]. Propensity score methods can be useful to reduce the number of covariates to be included in a multivariable model in case of limited sample size.…”
Section: Discussionsupporting
confidence: 90%
“…However, two studies 64,67 also came to the opposite conclusion, that estimates obtained from regression analysis and propensity scoring differ significantly. One simulation study 65 comparing the two methods considered propensity scoring to be the superior method, whereas another study 62 found that propensity scoring is superior when the number of events per confounder is low. The disparate results of these studies means that it is difficult to draw conclusions regarding the relative performance of the different approaches, but Kurth et al 64 make an important observation that potentially explains these different results.…”
Section: Effectiveness Of Adjustment Methodsmentioning
confidence: 99%
“…A summary of the studies that have looked at methods of adjustment for confounding bias in NRSs and how reliable they are [62][63][64][65][66][67][68][69][70] is presented in Appendix 3. Overall, it is unclear which methods are most appropriate in certain circumstances and further research is needed.…”
Section: Adjustment For Bias In Non-randomised Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…30,31 Recent research, however, has shown that PSM gives more accurate estimates of marginal treatment effects than traditional methods and that, in certain circumstances, the differences between the two approaches can be substantial. 32 One major advantage of PSM is that, unlike traditional regression methods, cases are only included in the analyses if satisfactory matching can be achieved. All analyses were undertaken using the PSMATCH2 program written for Stata.…”
Section: Approach To Analysismentioning
confidence: 99%